Holistic governance and meta-analysis on the sustainable ecological environment protection of the Lijiang River basin in China / Yang Liuyi ... [et al.] - Yang, Liuyi; Gunggut, Haijon; Tang, Howe Eng; Dusima, Haidy Henry; Huo, Tianze; Luo, Fengmao (Universiti Teknologi MARA Cawangan Sarawak, 2024)
Humans and nature are a natural community of destiny, dialectically united in their pursuit of sustainable development. The invaluable contribution of ecological and environmental resources to enhancing human life is undeniable. As there are still problems, in particular unclear rights and responsibilities of multiple subjects in the systemic management of the Lijiang River basin, this research aims to explore the current dilemmas of ecological environmental protection in the Lijiang River basin, and to improve the dilemmas from three elements, naming policy, authority and responsibility, and ecological environmental protection. This research conducts a case study on the systemic management of the Lijiang River Basin, employing questionnaires and interviews as primary research instruments. The questionnaire was answered by administrative law enforcement and judicial departments, experts, university students, and villagers along the river basin. Five individuals participated in interviews to gather feedback on the holistic governance of the Lijiang River Basin. The findings highlight the ecological and environmental protection dilemmas in the Lijiang River Basin and propose effective solutions based on the holistic theory from three perspectives. In terms of policy, the solution encompasses strengthening systematic planning, complementing overall planning, and focusing on macro support. In terms of authority and responsibility, the solution enlists strengthening intergovernmental communication and coordination, readjusting the organizational structure of departments, and strengthening the cooperation of multiple subjects. In terms of ecological environmental protection, the solution comprises strengthening risk prevention and resistance, focusing on prevention and supervision, and enhancing comprehensive repair capabilities.